2015
DOI: 10.1177/1539449214561763
|View full text |Cite
|
Sign up to set email alerts
|

Degree of Preference and Its Influence on Motor Control When Reaching for Most Preferred, Neutrally Preferred, and Least Preferred Candy

Abstract: The objective of this study was to determine whether reaching for objects with varying levels of preference associated with them elicited influenced motor control in a reaching task. Forty healthy adults were asked to reach for seven different types of candy, which they ranked by personal preference from being the most preferred to the least preferred. In this repeated measures design, data were analyzed on 39 participants who tended to demonstrate greater movement efficiency in movement time and movement unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 16 publications
1
28
2
Order By: Relevance
“…However, they also move faster toward that stimulus [1][2][3][4][5]. This suggests that reward and effort not only affect decision-making, they also influence motor control [6,7].…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…However, they also move faster toward that stimulus [1][2][3][4][5]. This suggests that reward and effort not only affect decision-making, they also influence motor control [6,7].…”
Section: Discussionmentioning
confidence: 87%
“…Equation 4 makes four predictions: as reward increases, the utility of the movement increases, but its optimum duration decreases ( Figure 1C). Animals should not only prefer stimuli that promise greater reward [12], but also move with greater speed toward them [1,2,4,5]. As the metabolic cost of the movement increases, the utility of the movement decreases, but its duration increases ( Figure 1D).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…For example, Sackaloo et al (2015) asked participants to rank order in terms of preference a number of different kinds of candy bars. When asked to reach for a single candy bar, participants reached faster and with a shorter duration for the more preferred bar.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that the value of a target affects the vigor of saccades (Xu-Wilson et al, 2009;Manohar et al, 2015;Reppert et al, 2015) and upper limb movements (Opris et al, 2011;Sackaloo et al, 2015;Summerside et al, 2018). Consistent with this, considerable evidence from monkey electrophysiology has revealed that regions of the dorsal parieto-frontal cortex, which directly contribute to goal-directed movements (Andersen and Cui, 2009), are modulated by incentives during movement preparation (Platt and Glimcher, 1999;Olson, 2003, 2004;Musallam et al, 2004;Leathers and Olson, 2012).…”
Section: Introductionmentioning
confidence: 87%